Land Suitability Evaluation for Durian (Durio zibethinus Murr.) Cultivation Based on Nutrient Retention - Bagas Dewa Setiawan; Purwadi Purwadi; Maroeto Maroeto (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2026)
Indonesia possesses vast land resources, offering significant potential for agricultural development. Among high-value commodities, durian (Durio zibethinus Murr.) is widely cultivated. Bumiaji District in Batu City, characterized by hilly topography and extensive agricultural land, serves as a prominent durian production center. Optimizing durian productivity, however, requires a thorough understanding of land suitability based on soil characteristics. This study evaluated land suitability for durian cultivation in Bumiaji District, focusing on key soil chemical properties, including soil pH, cation exchange capacity (CEC), base saturation (BS), and organic carbon (C-organic) content. The research was conducted using a survey method with purposive random sampling based on land mapping units (LMUs). Results indicated that most areas were classified as highly suitable (S1) based on CEC and organic carbon parameters, with CEC values ranging from 18.89 to 35.97 cmol/kg and C-organic levels above 1.2%. However, limitations were noted for pH and base saturation, with some areas classified as moderately (S2) or marginally suitable (S3). Improving land suitability can be achieved through targeted soil management strategies, such as liming with dolomite to enhance pH and base saturation. The findings of this study are expected to serve as a reference for implementing sustainable land management practices aimed at boosting durian productivity in Bumiaji District.